Pembrolizumab for the treatment of uveal melanoma: A case series - Jansen, Yanina Jeanne Leona (Rare Tumors, 2020)
Uveal melanoma is a rare disease. Up to 50% of the patients will develop metastases for which the treatment options are limited. No randomized controlled data for the treatment of uveal melanoma patients are available. In this study we describe the clinical course of nine uveal melanoma patients included in the pembrolizumab expanded access program (EAP) in Belgium. Nine uveal melanoma patients were treated in the EAP with 2mg/kg pembrolizumab every 3 weeks. Patients received pembrolizumab as first or second-line treatment. Baseline characteristics and tumor responses were prospectively collected. During a median follow-up of 40 weeks, the estimated median PFS was 18 weeks (95% CI 0.7–35) and median OS was 46 weeks (95% CI 33–59%). Four patients had stable disease (SD) for more than 20 weeks (PFS of 21, 22, and 27 weeks respectively) and 1 patient presented with SD for 119 weeks. No objective responses according to irRC were observed. One grade 3 hepatitis occurred which was reversible with the administration of high doses oral corticosteroids. Even though treatment with pembrolizumab is well tolerated, clinical benefit is disappointing. Nevertheless long-term diseases control can be achieved in selected cases